2012
DOI: 10.1007/s11102-012-0380-1
|View full text |Cite
|
Sign up to set email alerts
|

Cabergoline reduces cell viability in non functioning pituitary adenomas by inhibiting vascular endothelial growth factor secretion

Abstract: Dopamine (DA) therapy of non-functioning pituitary adenomas (NFA) can result in tumor stabilization and shrinkage. However, the mechanism of action is still unknown. Previous evidence showed that DA can inhibit pituitary vascular endothelial growth factor expression (VEGF), that may be involved in pituitary tumor growth. The aim of our study was to clarify whether VEGF secretion modulation might mediate the effects of DA agonists on cell proliferation in human NFA. We assessed DA receptor subtype 2 (DR2) expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 38 publications
0
18
1
Order By: Relevance
“…Octreotide was reported to down-regulate VEGF expression to achieve antiangiogenic effects on PAs [28]. Gagliano et al demonstrated that cabergoline reduces cell viability in non-functioning pituitary adenomas by inhibiting VEGF secretion, of which the modulation might mediate the effects of DA agonists on cell proliferation in nonfunctioning adenoma [29]. Interestingly, in present study, we did spearman's rank correlation analysis and found that D2R expression did not show a correlation with VEGF expression.…”
Section: Discussioncontrasting
confidence: 61%
“…Octreotide was reported to down-regulate VEGF expression to achieve antiangiogenic effects on PAs [28]. Gagliano et al demonstrated that cabergoline reduces cell viability in non-functioning pituitary adenomas by inhibiting VEGF secretion, of which the modulation might mediate the effects of DA agonists on cell proliferation in nonfunctioning adenoma [29]. Interestingly, in present study, we did spearman's rank correlation analysis and found that D2R expression did not show a correlation with VEGF expression.…”
Section: Discussioncontrasting
confidence: 61%
“…Cabergoline has been reported to decrease cell viability [44]. Ketoconazole has been demonstrated to decrease cell viability and also to promote the increased expression of apoptosis-related genes and cell cycle inhibitors in immortalized cell lines [45].…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies show that dopamine stimulation inhibits angiogenesis via decreased functions of VEGF and VEGF receptors in tumor tissues (Basu et al, 2001;Teunis et al, 2002;Asada et al, 2008). An in vitro study with non-functioning pituitary adenomas demonstrated that cabergoline, a dopamine D2 receptor (DR2) agonist, reduces VEGF secretion and cell viability, and that this inhibitory effect of cabergoline is blocked by sulpiride, a selective DR2 antagonist in DR2-expressing pituitary adenomas (Gagliano et al, 2013). Moreover, other animal studies with antipsychotics have suggested that risperidone and olanzapine increase the phosphorylation of the cAMP response element binding protein (CREB) in the hippocampus (Keilhoff et al, 2010;Réus et al, 2012), and that these antipsychotics enhance VEGF expression therein (Pillai and Mahadik, 2006;Keilhoff et al, 2010).…”
Section: Discussionmentioning
confidence: 99%